Jack Slade : song of the butcherbird - Gostick, Adrian Robert (Arcade Publishing, 2025)
A tale of frontier justice in the early days of the Pony Express--based on a story you'd never believe was true. Jack Slade is one of the few stationmasters on the Overland Stagecoach Company who has a code of honor and some skills with a wagon and a Colt. That's why he's chosen by company boss Benjamin Ficklin to clean out corruption on the line just as the Pony Express begins running. But Slade also has a soft spot for hard liquor. That's why he rides into Julesburg unarmed, and why he's filled with six bullets and some buckshot in broad daylight by Jules Beni, the corrupt old station master. Jack Slade: The Song of the Butcherbird is based on the true story of Slade's improbable survival, recovery, and redemption. With the help of his family; his loose-lipped, ne'er-do-well sidekick, Pete; and not a little liquid courage, Slade reluctantly returns to bring frontier law and justice to the plains--never again forgetting his revolver or Bowie knife. Perfect for readers of westerns, quintessential American historical fiction, and fans of Yellowstone, Jack Slade is a vivid animation of frontier life and justice in the early days of the Pony Express--dusty, unforgiving, and stained in blood.